Using the mTSES to Evaluate and Optimize mLearning Professional Development - Power, Robert Leo; Cristol, Dean; Gimbert, Belinda; Bartoletti, Robin; Kilgore, Whitney (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2016)
The impact of targeted professional development activities on teachers’ perceptions of self-efficacy with mobile learning remains understudied. Power (2015a) used the Mobile Teacher’s Sense of Efficacy Scale (mTSES) survey instrument to measure the effects of a mobile learning themed professional development course on teachers’ confidence with and interest in mobile learning. The current study looks at changes in perceptions of self-efficacy amongst participants in another open course about mobile learning called Instructional Design for Mobile Learning (ID4ML), which took place from May 4 – June 6, 2015 (Power, Bartoletti & Kilgore, 2015). The purpose of this study is to verify the reliability and construct validity of the mTSES instrument developed by Power (2015a, 2015b) and Power, Cristol and Gimbert (2014), and to explore trends in self-efficacy changes amongst a more diversified participant population. This paper reports on the findings from the analysis of data collected using the mTSES tool. The findings provide useful feedback on the impacts of participating in the ID4ML course. They also provide further support for the utility of the mTSES instrument as a measure of perceptions of self-efficacy with mobile learning. These findings point to the potential utility of the mTSES as a tool for both planning and evaluating mLearning professional development training for teachers.